Ontology-Based Customisation Management System for Driver-Vehicle Interfaces: A Preventive Approach to Incident Reduction and Legal Accountability in Highly Automated Vehicles - Maria Assunta Cappelli; Giovanna Di Marzo Serugendo (Applied Sciences, 2025)
This study presents the development of an ontology-based customisation management system (Onto-CMS) for driver–vehicle interfaces (DVIs) in highly automated vehicles (HAVs). The objective of the proposed system is to enhance safety, minimise the probability of accidents and address legal liability concerns. The study highlights the importance of DVIs in automated vehicles and the need for safe and adaptable options for human drivers, while also considering the legal implications associated with the development of these interfaces. The research identifies the shortcomings of existing systems and proposes the Onto-CMS as a more effective alternative solution. The proposed system facilitates additional personalisation tasks and demonstrates higher performance compared to systems lacking ontological structuring. Indeed, the Onto-CMS allows dynamic adaptation to individual preferences while maintaining the integrity of standardised safety elements. It is distinguished by its ability to adjust to diverse contexts, such as those involving impaired drivers, without compromising critical safety standards. The onto-CMS reduces the need for recurrent revisions and improves operational productivity and overall usability. The results show that the Onto-CMS improves the configuration of DVIs by providing customised, scalable and context-aware alternatives. The study provides a basis for further research that could extend the system’s capabilities to cover a wider range of driver characteristics and requirements.